Assessment of absenteeism related to oral disorders among police officers and firefighters of São Paulo state - a census cohort study (Research, Society and Development, 2022)
Absenteeism due to illness is recognized as a global public health problem, with major economic and social impacts. Furthermore, information about these conditions among firefighters, police officers, and other professionals in the military forces is very scarce. Thus, the present study aimed to evaluate dental absenteeism of the staff of the Military Police of São Paulo state in 2017. For this, demographic and functional data and information related to the type of absence from work were collected (logistic platform GIS - Health) to calculate odds ratios among socio-demographic and functional variables and convalescence (absence of up to 10 days). The index of severity, frequency, and mean duration of dental absences were also calculated, comparing them with sick leaves during the same period as well. We could identify 80,928 absences related to oral conditions. Functional, socio-demographic, and dental disease characteristics were associated with convalescence, i.e., officers over 50 years old, from the countryside, and in a work leave situation due to caries lesions, dental pulp conditions, or periodontal disease, were associated with absenteeism of up to 10 days. In the Military Police, in 2017, there was an average loss of work period of 2h/person/year exclusively from dental reasons. The mean duration of absences was 2.21 days. Thus, it seems that the older the officers and the further away from the capital of São Paulo, the longer the period of work absence. Furthermore, aging in the occupational context is a strong factor for absenteeism. Caries lesions and periodontal disease are also highly related to absenteeism when compared to other dental diseases.